A cyclic algorithm for the split common fixed point problem of demicontractive mappings in Hilbert spaces - Tang, Yu-Chao; Peng, Ji-Gen; Liu, Li-Wei (Mathematical Modelling and Analysis, 2012)
The split common fixed point problem has been investigated recently, which is a generalization of the split feasibility problem and of the convex feasibility problem. We construct a cyclic algorithm to approximate a solution of the split common fixed point problem for the demicontractive mappings in a Hilbert space. Our results improve and extend previously discussed related problems and algorithms.